Geographical Influences on the Language Skill of Elementary School Students in Lae-Lae Island Makassar City - Yusri Yusri; Andi Reza Hidayat (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This article describes how geographic factor influences students’ language skill which in this case is the mastery of vocabularies. This study is a quantitative research with sociolinguistic approach. The respondents of this study were elementary school students that live in Lae-Lae Island, Makassar City, and as for the comparison the researcher took other respondents from other elementary schools in urban areas. The researcher selected 30 students from each school. The techniques used in this study were a vocabulary mastery test, observations, and interviews. The data analysis technique is descriptive analysis and independent sample t test. The result indicates that there are significant geographical factors on the students’ vocabulary mastery. Elementary students in urban area have higher skill in mastering vocabularies than those in Lae-Lae Island. In addition, the geographical factors also influence the type of their vocabularies mastered by the students. The students from Lae-Lae Island are better in mastering marine vocabularies than those of urban areas.